Relationship of Secure Attachment to Fathers and Mothers with Emotional Intelligence in Junior High School Adolescents: Hubungan Secure Attachment pada Ayah dan Ibu dengan Kecerdasan Emosi pada Remaja di Sekolah Menengah Pertama - Yanti, Rachma Aulia Prima; Mariyati, Lely Ika (Indonesian Journal of Innovation Studies, 2023)
This study was conducted with the aim of revealing whether or not there is a relationship between secure attachment to fathers and mothers with emotional intelligence in adolescents at SMP Negeri 2 Sedati. The research method used is correlational quantitative. The variables in this study are secure attachment to the father and secure attachment to the mother as the independent variable and emotional intelligence in adolescents as the dependent or dependent variable. This research was conducted at SMP Negeri 2 Sedati with 198 students as the sample using proportionate stratified random sampling technique. Data analysis was performed by multiple regression correlation analysis using the JASP 0.14.1.0 program. based on the results of data analysis showed a positive relationship between secure attachment to father and mother with emotional intelligence with an F value of 73,958 and a significance of p < 0.001 which means that the hypothesis in this study can be accepted with an effective contribution of 43.1% which indicates that secure attachment to father and mother effect on adolescent emotional intelligence.